Exhaled nitric oxide in asthma: from diagnosis to management. Issue 1 (24th February 2023) - Guida, Giuseppe; Carriero, Vitina; Bertolini, Francesca; Pizzimenti, Stefano; Heffler, Enrico; Paoletti, Giovanni; Ricciardolo, Fabio L.M.
Abstract : Purpose of review: Exhaled nitric oxide (FE NO) is a noninvasive marker of eosinophilic airway inflammation, therefore, highly informative in asthma. Although FE NO measurement is a potentially accessible tool to many physicians, recommendations regarding its clinical utility in diagnosing or tailoring treatment have not reached the expected diffusion. More recently FE NO emerged as a biomarker for type-2 asthma phenotyping and a predictor of response to biologics. Recent findings: The physiological discoveries and relevant acquisitions in clinical practice regarding FE NO in asthma are presented. The FE NO story draw a wavy path, characterized by promising findings, exciting confirmations and periods of low visibility. FE NO emerged as a tool to increase the probability of asthma diagnosis. FE NO predicts response to inhaled glucocorticoids (ICS), favoring the development of tailored treatment strategies and unrevealing nonadherence to ICS in difficult-to-treat or uncontrolled asthma. Finally, FE NO was associated with a more severe phenotype and became a consolidated biomarker of type-2 inflammation. Summary: FE NO demonstrated to be a noninvasive and very reproducible test, encompassing many applications in the field of asthma management. Its routinely use, according to international guidelines, may improve the quality of patient assistance, from difficult-to-treat cases to biologic monitoring.